Large dynamic covariance matrices - Robert F. Engle; Olivier Ledoit; Michael Wolf (University of Zurich, Department of Economics, 2017)
Second moments of asset returns are important for risk management and portfolio selection. The problem of estimating second moments can be approached from two angles: time series and the cross-section. In time series, the key is to account for conditional heteroskedasticity; a favored model is Dynamic Conditional Correlation (DCC), derived from the ARCH/GARCH family started by Engle (1982). In the cross-section, the key is to correct in-sample biases of sample covariance matrix eigenvalues; a favored model is nonlinear shrinkage, derived from Random Matrix Theory (RMT). The present paper marries these two strands of literature in order to deliver improved estimation of large dynamic covariance matrices.
Keywords: C13; C58; G11; 330; Composite likelihood; dynamic conditional correlations; GARCH; Markowitz portfolio selection; nonlinear shrinkage